The growth response of pokem (Setaria italica L.) inoculated with arbuscular mycorrhizal fungi (AMF) from tailings area - Suharno Suharno; Retno Peni Sancayaningsih; Endang Sutariningsih Soetarto; Rina Sri Kasiamdari (Brawijaya University, 2021)
The purpose of this research was to study the growth response of pokem (Setaria italica), which was inoculated by the arbuscular mycorrhizal fungi (AMF) from the tailings area. The method used in this research was a completely randomized design of factorial pattern. The factors consisted of AMF types (M)(M0: non-mycorrhizal, M1: Claroideoglomus etunicatum BGR, M2: C. lamellosum B1107S, M3: C. etunicatum L3101D), and inoculum density (I) (I: 5 g, II: 10 g per pot of planting media) with 8 replicates. The source of inoculum C. lamellosum B1107S and C. etunicatum L3101D originated from tailings in the gold mining area of Timika. The results showed that inoculation of C. etunicatum L3101D could increase the plant growth better than C. etunicatum BGR and C. lamellosum B1107S. Significant growth occurred on the parameters of the height of the plants, leaf area, dry weight and fresh weight of the plants, relative growth rate, and phosphorus absorption by the plants. The amount of nitrogen tended to decrease with AMF treatment, but it was not significant, whereas K has insiginificantly increased. The propagule density treatment increased plant growth on all parameters. The best growth occurred if the type C. etunicatum L3101D was inoculated with 10 g of propagule per planting media.